2017
DOI: 10.18632/oncotarget.15421
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors involvement in intervertebral discogenic pain of the elderly women: colocalization and correlation with the expression of Substance P in nucleus pulposus

Abstract: Estrogenic modulation of pain is an exceedingly complex phenomenon. However, whether estrogen is involved in discogenic low back pain still remains unclear. Here, immunoreactivity staining technique was used to examine the expression level of the estrogen receptors (ERα and ERβ) and a pain related neuropeptide, Substance P in the lumbar intervertebral discs to analyze the relationship between the ERs and Substance P. Nucleus pulposus tissues of 23 elderly female patients were harvested during spinal surgeries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 60 publications
2
25
1
Order By: Relevance
“…An upregulated CGRP and SP expression has been reported in sensory nerves innervating degenerated IVD in DDD patients [5,6,7]. Furthermore, an increased SP expression has been reported in TNF-α stimulated human NP cells and in NP tissues extracted from elderly female DDD patients [39,40]. However, we could not observe higher SP levels in IVD tissues collected from DDD patients in comparison to PM controls.…”
Section: Discussioncontrasting
confidence: 60%
“…An upregulated CGRP and SP expression has been reported in sensory nerves innervating degenerated IVD in DDD patients [5,6,7]. Furthermore, an increased SP expression has been reported in TNF-α stimulated human NP cells and in NP tissues extracted from elderly female DDD patients [39,40]. However, we could not observe higher SP levels in IVD tissues collected from DDD patients in comparison to PM controls.…”
Section: Discussioncontrasting
confidence: 60%
“…It has been reported that in DDD patients, the sensory nerves innervating degenerative IVD will up-regulate the expression of CGRP and SP ( Richardson et al, 2009 ; Krock et al, 2014 ). In addition, increased expression of SP was found in human nucleus pulposus (NP) cells stimulated by TNF-α and NP tissues extracted from elderly female DDD patients ( Song et al, 2017 ). Studies have shown that SP and CGRP are the main peptidergic neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…We show that raloxifene also has promise as an IVD therapeutic and we suggest that raloxifene may impact the IVD by at least three mechanisms. Firstly, compared to men, women have low discogenic expression of er-α protein, which may limit raloxifene-induced proliferation (30,34) and both lower er-α and aging can increase pain-related SP in the IVD (38) . Therefore, raloxifene may reduce back (21) and joint pain (49) in post-menopausal women because of estrogen-induced reduction of SP in the IVD and bone.…”
Section: Discussionmentioning
confidence: 99%
“…For cell quantification in the NP or AF, the image was thresholded for intensity to demarcate the positive cell by semi-automation using ImageJ (NIH). Quantitative PCR was accomplished as previously described (38) . Briefly, relative gene expression was normalized to 18s (Hs99999901_s1) for each sample and then experimental values were normalized to the CON average CT value (2 −ΔΔCT ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation